Higher education and Sustainable Development Goals during COVID-19: coping strategies of a university in Wuhan, China - Suyu Liu (SAGE Publishing, 2020)
Background It is widely perceived that COVID-19 has significant influence on higher education and also contribution to development including Sustainable Development Goals (SDGs). However there is insufficient evidence about investigations on such influences, especially at micro level. Design and method A university located in Wuhan, China, was selected for the case study to explore how COVID-19 affects higher education and how universities' coping strategies of COVID-19 can contribute to SDGs. The method is an analysis of 32 institutional documents published by the university. Results The university in the case study has taken a number of coping strategies of COVID-19, largely in four aspects including medical services, online education, logistic support, and graduate employment promotion. These coping strategies contribute to achieving SDGs, especially SDGs 1, 3, 4, 5, 8, and 10. Conclusions The case study provides micro-level empirical evidence, which supports that appropriate university coping strategies of COVID-19 can contribute to SDGs, even it is widely perceived that the pandemic has brought strong negative impact on higher education and sustainable development. The selection of a university in Wuhan, China can generate more practical implications, as Wuhan is the first city that experienced the unprecedented lockdown, and China is the first country which reopened university campuses after the lockdown.